2020
DOI: 10.18488/journal.61.2020.83.615.624
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pedagogical Hypermedia on Acquisition of Scientific Concepts among Primary School Students

Abstract: This study examined the effect of a Pedagogical Hypermedia Environment in the Science Discipline (PHFSD) on the acquisition of scientific concepts among fifthgraders during the 2019-2020 school years. The study adopted a quasi-experimental method with 50 fifth-grade students from a private school in Amman, Jordan, divided into two groups of 25 each. Students were randomly assigned to either a control group that was taught using traditional methods or an experimental group that was taught using PHFSD. A scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Although the three-way interaction effect subsumes the main effect of treatment, it is important to underscore the treatment effectively facilitated the conceptual change of the learners compared to the control group given the large effect size. This is in line with the findings of Ajlouni & Jaradat (2020) which showed that Jordanian primary school pupils who were exposed to pedagogical hypermedia acquired scientific concepts more than those in the control. The study found out that the treatment accounted for 70% of total variance of the conceptual change score.…”
Section: Resultssupporting
confidence: 91%
“…Although the three-way interaction effect subsumes the main effect of treatment, it is important to underscore the treatment effectively facilitated the conceptual change of the learners compared to the control group given the large effect size. This is in line with the findings of Ajlouni & Jaradat (2020) which showed that Jordanian primary school pupils who were exposed to pedagogical hypermedia acquired scientific concepts more than those in the control. The study found out that the treatment accounted for 70% of total variance of the conceptual change score.…”
Section: Resultssupporting
confidence: 91%
“…The findings of this study are in line with the results of several other studies relating to hypermedia. First, Ajlouni and Jaradat [8] found a significant positive impact of hypermedia on acquiring transparent science concepts. Then, Bunga et al [10] showed that hypermedia increased students' scientific processing skills and made physics content easier to understand.…”
Section: Resultsmentioning
confidence: 99%
“…ERs can foster collaboration skills, problem-solving, and critical and innovative thinking. They can also enhance the learning experience through hands-on and mind-on learning; provide a fun, exciting, and engaging learning environment; and motivate students to learn, provide opportunities to link learning with practice, develop students' technological competencies, enhance student motivation to learn, encourage imagination, improve academic achievement [8], [39], [52][53][54][55][56][57].…”
Section: Educational Robots and Science Education Contextmentioning
confidence: 99%
See 2 more Smart Citations